Comparison of the Use of Discourse Markers in English Political Speeches between Native and Non-native Speakers - Dewayanti, Wanda Dewi; Widhiyanto, Widhiyanto; Sakhiyya , Zulfa (Universitas Islam Negeri Palopo, 2025)
This study aims to analyze the use of Discourse Markers (DMs) in politicians' speeches on the USINDO YouTube Channel. DMs are used to organize, manage, and connect communication. Then politics becomes a public concern and USINDO becomes one of the signs of bilateral relations between Indonesia and America. The analysis was conducted from the speeches of four politicians, two from Indonesia as non-native speakers and two from America as native speakers, and used Fraser's 2009 theory. It was found that 670 markers were used by Native and Non-native. Namely Contrastive Discourse Markers (CDMs), Elaborative Discourse Markers (EDMs), and Inferential Discourse Markers (IDMs). The frequent markers found are EDMs such as 'and', CDMs such as 'but', and IDMs such as 'so'. Furthermore, both native and non-native speakers of English use DMs in political speeches for similar purposes, such as organizing discourse, managing transitions, clarifying points, and ensuring politeness. Then the different DMs are used more often, organically, and successfully in political speeches by native English speakers, who also have a more varied understanding of its use and do not use overlapping double markers.